Flexible learning during educational disruption: a case study of teaching integrated circuits design - Welsen, Sherif; Morgan, Peter; Walker, James (IEEE, 2020)
To date, there has been little written that explains how engineering-related tuition can be rapidly and effectively moved online. Furthermore, there is sparse literature written that focuses on how students can adapt to such technologies in a relatively short space of time. Finally, it is both necessary and prudent to increase discourse on the effective online teaching of technical design subjects. This paper evaluates the effectiveness of online tools such as interactive live lectures, slide annotation, and electronic whiteboard, for engaging students in electrical and electronic engineering education. The paper advances those debates by providing an evaluative analysis from the perspective of students taking an Integrated Circuits design module that was delivered during the 2020 COVID-19 crisis. The major research question is: to what extent do electrical engineering students perceive online learning tools to be useful in enhancing their sudden learning change? Responses were collected using an online questionnaire that was offered to 23 students who enrolled in the module, and a 70% completion rate was received. The findings showed that students engaged well with the technologies, and they found them easy to use and beneficial for their learning.